Modern Parliament Image: Managing Transparency, Information Technology and Representation - Elly Yuliawati; Ispawati Asri (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
The People's Legislative Council of the Republic of Indonesia (DPR RI), like parliaments in other countries, is developing its institutional governance towards a modern parliament. The idea of a modern parliament is a strategy to increase public trust in the DPR RI. This study aims to generate public views about the image of a modern parliament as the embodiment of good government governance. Using the case study method to find the actual image representation. Conducting interviews with various sources of information both internal and external stakeholders and also reviewing documents for the validity of the data. The study found that the achievement of modern parliamentary indicators, namely transparency, technology, and representation, was still experiencing obstacles in the form of not fulfilling these three indicators. Of the three, only technology indicators have shown their best achievements in the form of easy public access to official information on the parliament website. Transparency and representation have not been fully open and in accordance with public expectations. Seen by the large number of public participation in the form of criticism, suggestions, proposals that oversee the performance of the parliament. This study concludes that the modern parliament as an embodiment of good governance in the Indonesian Parliament is carried out through strengthening the aspects of transparency, technology and representation. Efforts towards a modern parliament in realizing good governance still need time and follow the dynamics of society and the changing times.